Endoscopic Management of Pancreaticopleural Fistula in a Child with Hereditary Pancreatitis - Lee, Dahye (Pediatr Gastroenterol Hepatol Nutr, 2019)
Pancreaticopleural fistula (PPF) a fistulous connection between the pancreas and pleural space due to prolonged chronic pancreatitis (CP). PPF is a very rare complication which presents in 0.4% of chronic pancreatitis cases, especially among children. We report a case involving a 3-year-old boy who presented with pleural effusion caused by a PPF, a complication of hereditary pancreatitis, which was, for the first time in Korea, successfully managed with endoscopic treatment. Chest radiography and computed tomography showed massive pleural effusion. Percutaneous catheter drainage was performed. High amylase levels were observed in the pleural fluid and serum, suggesting PPF. The patient was managed with bowel rest and octreotide infusion. Endoscopic retrograde cholangiopancreatography revealed CP, and pleural effusion was successfully managed with stent placement. PRSS1 genetic screening revealed R122H mutation.